2022
DOI: 10.1002/app.53297
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization effect of cellulose paper and postcuring conditions on the mechanical properties of flax fiber reinforced epoxy biocomposite

Abstract: An ever‐increasing rise in demand for sustainable materials has received significant attention in developing biocomposites for structural applications. In this regard, natural fibers replacing synthetic fibers as reinforcement in epoxy composite could be a significant gain toward sustainability, especially in automobile and structural applications. Herein, flax fiber/cellulose paper–reinforced epoxy biocomposite (FREC‐X) was fabricated via a vacuum infusion process. The influence of postcuring conditions (time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In spite of the addition of nanoparticles, including silica, TiO 2 , Al 2 O 3 , 11,12 and two‐dimensional materials, 13 graphene, for instance, can effectively improve the mechanical properties of EP, one‐dimensional materials, such as carbon nanotube and various fibers, undoubtedly, are a better choice 14–16 . It has been reported that diverse fibers, including basalt fiber, glass fiber, carbon fiber, and flax fiber, show obvious enhancements in the mechanical properties of EP due to their great strength, low density, creep resistance, good corrosion resistivity, and so on 6,17–19 . Therefore, great attention has already been focused on utilizing versatile fibers in developing EP composites for commercial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the addition of nanoparticles, including silica, TiO 2 , Al 2 O 3 , 11,12 and two‐dimensional materials, 13 graphene, for instance, can effectively improve the mechanical properties of EP, one‐dimensional materials, such as carbon nanotube and various fibers, undoubtedly, are a better choice 14–16 . It has been reported that diverse fibers, including basalt fiber, glass fiber, carbon fiber, and flax fiber, show obvious enhancements in the mechanical properties of EP due to their great strength, low density, creep resistance, good corrosion resistivity, and so on 6,17–19 . Therefore, great attention has already been focused on utilizing versatile fibers in developing EP composites for commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] It has been reported that diverse fibers, including basalt fiber, glass fiber, carbon fiber, and flax fiber, show obvious enhancements in the mechanical properties of EP due to their great strength, low density, creep resistance, good corrosion resistivity, and so on. 6,[17][18][19] Therefore, great attention has already been focused on utilizing versatile fibers in developing EP composites for commercial applications. Basalt fibers are bio-based fibers obtained from basalt rocks and have been widely used in many engineering fields.…”
mentioning
confidence: 99%